“I think they are infected because of their ignorance and lack of responsibility”: A mixed-methods study on HIV-related stigma in the healthcare system in Kazakhstan - Balnur Iskakova; Elizabeth J. King; Recai Murat Yucel; Jack DeHovitz; Zhamilya Nugmanova (PLoS ONE, 2025)
Background HIV-related stigma among healthcare providers remains a significant barrier to effective HIV care and treatment. This study aimed to assess HIV-related stigma and associated factors among healthcare providers in primary healthcare clinics (PHCs) in Almaty, Kazakhstan. Methods A mixed-methods design was employed, involving quantitative surveys and qualitative in-depth interviews. Eight PHCs were randomly selected, and 448 healthcare providers participated in the survey. The cross-sectional surveys took place at the PHCs between May 2, 2019, and July 2, 2019. The sample size was predetermined statistically with a 2.5% precision using a 95% confidence level. For the qualitative component, 10 participants were chosen for in-depth interviews. Descriptive statistics, bivariate analysis, and multivariable logistic regression models were performed for quantitative data analysis. Qualitative data were analyzed through manual thematic analysis. Results The study revealed high levels of HIV-related stigma, with 87% of respondents agreeing with at least one stigmatizing statement about people living with HIV (PLHIV). Fear of HIV infection was also prevalent, with 85% of healthcare providers expressing some level of concern about contracting HIV during medical procedures. Logistic regression analysis indicated that longer years of work in healthcare were protective against stigmatizing opinions (Adjusted Odds Ratio (AOR)=0.25; 95% Confidence Interval (95%CI)=0.09,0.67; p = 0.006), while not having seen a patient living with HIV in the last 12 months was associated with higher stigma (AOR = 3.31; 95%CI = 1.73, 6.31; p < 0.001). Qualitative interviews corroborated these findings and highlighted differential attitudes towards PLHIV based on modes of transmission, with particularly negative views towards sex workers and individuals with non-traditional sexual orientations. Conclusions The study demonstrates significant HIV-related stigma among healthcare providers in Almaty PHCs, influenced by a lack of exposure to PLHIV and specific socio-demographic factors. These findings underscore the need for targeted interventions to reduce stigma and enhance HIV care in Kazakhstan.